1988
DOI: 10.3109/10915818809019540
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of Neosugar: Genotoxicity, Carcinogenicity, and Chronic Toxicity

Abstract: Neosugar, a fructooligosaccharide mixture, was tested for genotoxicity in three assays:(1) microbial reverse mutation assays in Salmonella typhimuriyn (Ames assay) and Eschericliia coli WP2 uvrA, (2) the L5178Y mouse lymphoma TK mammalian cell mutation assay, and (3) an assay for the induction of unscheduled DNA synthesis (UDS) in human epithelioid cells (HeLa S3). Each assay was conducted at a wide range of dose levels, both with and without metabolic activation. Test results gave no indication that neosugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…First, the safety of the ingredient must be assessed. The safety of FOS has been documented in various studies (Clevenger et al, 1988;Hidaka et al, 1986;Tokunaga et al, 1989). Furthermore, Tokunaga et al (1986) demonstrated no significant adverse effects occurred in rats with doses up to 1.67 g/day.…”
Section: Introductionmentioning
confidence: 93%
“…First, the safety of the ingredient must be assessed. The safety of FOS has been documented in various studies (Clevenger et al, 1988;Hidaka et al, 1986;Tokunaga et al, 1989). Furthermore, Tokunaga et al (1986) demonstrated no significant adverse effects occurred in rats with doses up to 1.67 g/day.…”
Section: Introductionmentioning
confidence: 93%
“…Onion has the highest content of scFOSs, ranging from 25-40% (dry matter basis) (Clevenger et al, 1988). Onion has the highest content of scFOSs, ranging from 25-40% (dry matter basis) (Clevenger et al, 1988).…”
Section: Short-chain Fructooligosaccharides (Scfos)mentioning
confidence: 99%
“…They consist of sucrose molecules to which 1, 2 or 3 additional fructose units are added by a b-(2-1)-glycosidic linkage to the fructose unit of sucrose (Clevenger et al, 1988). They are manufactured either from sucrose by transfructosylation or from inulin by controlled enzymatic hydrolysis (Crittenden & Playne, 1996).…”
Section: Introductionmentioning
confidence: 99%